PELAKSANAAN INTERNALISASI NILAI-NILAI KARAKTER DALAM PEMBELAJARAN IPS KELAS VII E SMP N 12 PONTIANAK - Petronita Yolenta; F.Y Khosmas; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract This research aimed to find out the "Implementation of Internalization of Character Values in Social Study in Class VII E ofSMP N 12 Pontianak". The problem in this research was How the Implementation of Internalization of Character Values in Social Study in Class VII E of SMP N 12 Pontianak. The sub-problems in this research was how the implementation of the internalization of character values in social study namely Love of God and all of his creations, Independence and Responsibility, Honesty, Trust and Wisdom, Respect and courtesy, Generous, helpful and mutual cooperation, Confident, creative, and hard-working, leadership and justice, kind and humble, tolerance, peace and unity. The variable in this research was a single-variable, namely "Implementation of Internalization of Character Values in Social Study". The data sources in this research were students and the teacher of Class VII E, the research method used is a qualitative method in the form descriptive research. Datacollection techniques in this research are direct observation, interviews, and documentation. The results of this research indicated that the implementation of Internalization of character values in social study in class VII E has been classified as good. Keywords: Character Values,Internalization, Social Study